Electronic structure and optical properties of boron suboxide B6O system: First-principles investigations. (October 2016) - Wang, Jinjin; Wang, Zhanyu; Jing, Yueyue; Wang, Songyou; Chou, Che-Fu; Hu, Han; Chiou, Shan-Haw; Tsoo, Chia-Chin; Su, Wan-Sheng
Abstract: The structural, mechanical, electronic, and optical properties of B6 O were explored by means of first-principles calculations. Such a system is mechanically stable and also a relatively hard material which are derived from obtained elastic constants and bulk moduli. Bulk B6 O is a direct-gap semiconductor with a bandgap of about 2.93 eV within G0 W0 approximation. Furthermore, the optical properties, such as real and imaginary parts of dielectric functions, refractive index and extinction coefficient, and the comparison of optical properties between the density-functional theory (DFT) and G0 W0 Bethe–Salpeter equation (G0 W0 -BSE) results, were computed and discussed. The results obtained from our calculations open a possibility for expanding its use in device applications. Highlights: The structural, mechanical, electronic, and optical properties of B6 O were explored by means of first-principles calculations. Such a system is mechanically stable and also a relatively hard material. This bulk B6 O is a direct-gap semiconductor with a bandgap of about 2.93 eV within G0 W0 approximation. The optical properties, such as real and imaginary parts of dielectric functions, refractive index and extinction coefficient, and the comparison of optical properties between the density-functional theory (DFT) and Bethe–Salpeter equation (BSE) results, were computed and discussed.